Risk, resilience and identity construction in the life narratives of young people leaving residential care. Issue 2 (6th June 2016) - Schofield, Gillian; Larsson, Birgit; Ward, Emma
Abstract: The role of residential care for children has developed very differently internationally, but in all cultural contexts, there are questions about the extent to which it can help young people recover from high risk backgrounds. In the UK, residential care has come to be seen as the placement of last resort, yet new government guidance on permanence has suggested that residential care can provide security and a sense of belonging. Narrative analysis of interviews with 20 care leavers identified their different pathways from birth families through residential care to early adulthood. Some experienced a transformation from a negative sense of self as victims or 'bad children' to survivors, while others continued to struggle. Key to successful turning points were four interacting factors, all associated with resilience; connection, agency, activity and coherence. These narratives revealed the importance of nurturing relationships and a sense of 'family', and also the role of support after leaving residential care, when transitions workers helped them to move on but stay connected. The study highlighted how residential care leavers from adverse backgrounds attribute very different meanings to their experiences, which affects identity construction, resilience and the need for support.